Effect of the ensiling time of hydrated ground corn on silage composition and in situ starch degradability - Arcari, Marcos André; Martins, Cristian Marlon de Magalhães Rodrigues; Tomazi, Tiago; Santos, Marcos Veiga dos (Brazilian Journal of Veterinary Research and Animal Science, 2016)
The aim of this study was to evaluate the effect of time of ensiling on chemical composition and in situ degradability of starch of hydrated ground corn (HGC) with medium grain vitreousness. Corn grains harvested at 83% of dry matter (DM) and vitreosity content of 67% ± 3, were dried to 87% DM. Grains were milled into a device with 2 mm sieve, reconstituted to reach 67% DM, and ensiled (density of 880 Kg/m³) for up to 330 days. One HGC sample was collected monthly for in situ determination of composition, fermentation end products and for corn starch degradability. Ensiling time did not affect the DM and crude protein (CP) content of the HGC. However, starch concentration was reduced by 2.4 percentage points at 330 days compared to 3 days of ensiling. Increased concentrations of NH3-N (8.5 times), lactic acid (3.45 times), acetic acid (4.1 times), propionic acid (1.7 times), butyric acid (2.8 times) and alcohol (2.4 times) were observed during the ensiling period. The rapidly degradable fraction (fraction A) and the rate of degradation of the slowly degradable fraction (fraction C) of HGC starch were increased 3.51 and 2.21 times, respectively, during the ensiling period. Conversely, the slowly degradable fraction (fraction B) of the HGC starch was decreased 1.93 times during the ensiling period. The effective degradability of the starch of HGC increased for passage rates by 0.02/h (79.9% vs. 94.5%); 0.05/h (65.9% vs 90.01%) and 0.08/h (56.98 vs. 86.52%) when it was evaluated at 3 vs 330 days of ensiling, respectively. In conclusion, ensiling time affected the chemical composition and increases rumen starch degradability of HGC with medium vitreousness of the grain endosperm.